Answer:
![6000 = 3000(1+0.0424)^(t)](https://img.qammunity.org/2023/formulas/mathematics/college/sxad65v2h9olspra6v9uyfsa50hnqlz7bc.png)
t = 16.73 years
Explanation:
This can be solved using the "exponential growth" formula.
Steps:
A = Final Amount
S = Starting Value
r = rate
c = times in a year ( c = 1 in this equation which is why it's not shown in the actual equation )
1.
→ cancel out S →
2.
→ sperate ct from equation by logging both sides (logging a value with an exponent brings the exponent in front of log) →
![log((A)/(S)) = ctlog(1+(r)/(c))](https://img.qammunity.org/2023/formulas/mathematics/college/otzbj83xcn9vwv94wqelnl2lj5iyj09djk.png)
3.
→ transfer right side log to left side along with the c value to only have t remaining →
![(log((A)/(S)))/(clog(1+(r)/(c))) = (ctlog(1+(r)/(c)))/(clog(1+(r)/(c)))](https://img.qammunity.org/2023/formulas/mathematics/college/3nd5yvha6cs9k8vpledw4hw73wj24qjbg7.png)
4. Solve for answer:
![(log((A)/(S)))/(clog(1+(r)/(c))) = t](https://img.qammunity.org/2023/formulas/mathematics/college/i2e7kjp12u7kk3v84iorp2m6eew9gp4eom.png)